Relationship between different measures of aerobic fitness and repeated-sprint ability in elite soccer players - da Silva, J. F.; Guglielmo, L. G. A.; Bishop, D. (The Journal of Strength and Conditioning Research, 2010)
The main purpose of this study was to investigate the relationship between physiological variables related to aerobic fitness (maximal oxygen uptake: Vo2max; the minimum velocity needed to reach VO2max: vVO2max; velocity at the onset of blood-lactate accumulation: vOBLA) and repeated-sprint ability (RSA) in elite soccer players. Twenty-nine Brazilian soccer players (17.9 ± 1.0 years; 178.7 ± 5.2 cm; 73.6 ± 6.7 kg; 11.1 ± 1.3% body fat) from 2 national level teams (A, B) took part in the study. Subjects first performed an incremental test on a treadmill to determine their VO2max, vVO2max and vOBLA. After at least 48 hours, subjects performed an RSA test consisting of 7 34.2-m sprints interspersed with 25 seconds of active recovery, to determine the mean time (MT), the fastest time (FT) and the Sprint decrement (Sdec). Pearson product moment correlations and multiple regressions were used to assess the relationship between aerobic fitness and RSA variables (FT, MT, Sdec, [La] Peak). An analysis of variance, followed by a post hoc test (Tukey), was used to compare the 7 sprints of the RSA test. The level of significance was set at p < 0.05. A significant negative correlation was found between both vOBLA and vVO2max and MT during the RSA test (r = -0.49, p < 0.01; r = -0.38, p < 0.05, respectively). There were also negative correlations between Sdec and vOBLA (r = -0.54), vVo2max (r = -0.49) and Vo2max (r = -0.39). The multiple regression revealed that the aerobic (vOBLA) and anaerobic (FT) components explained approximately 89% of the variance of MT. The results of this study demonstrated that RSA is more strongly correlated with vOBLA and vVo2max than the more commonly measured VO2max.